Posture Status Differences Between Preschool Boys and Girls - Anida Kapo-Gurda; Amin Efendić; Indira Mahmutović; Siniša Kovač; Husnija Kajmović; Safet Kapo; Jožef Šimenko (Journal of Functional Morphology and Kinesiology)
Background/Objectives: The preschool period plays an essential role in shaping a child’s overall development, which influences physical, emotional, social, and cognitive growth. At this stage, establishing proper postural habits is essential, as it can have lasting effects on health, well-being, helps to prevent future issues, and supports overall development. Therefore, the present work aims to determine the differences in postural status between boys and girls of preschool age. Methods: The sample of participants consisted of 92 children (n = 46 boys and n = 46 girls); the average age for girls was 5.41 ± 0.30 years and for boys it was 5.53 ± 0.31 years. Data were collected using licensed state-of-the-art diagnostic equipment, Contemplas 3D Posture Compact, using 16 variables to assess postural status with a Mann–Whitney U test. Results: The results of this study indicate that boys have more pronounced deformities in the following variables: shoulder displacement (p = 0.047), pelvic obliquity (p = 0.000), sag. distance cervical spine–sacrum (p = 0.029), sag. distance thoracic spine–sacrum (SDTS) (p = 0.016), and sag. distance lumbar spine–sacrum (SDLS) (p = 0.005). Conclusions: This study confirmed gender differences in postural characteristics in preschool children. Boys showed a greater tendency towards postural deviations, indicating the necessity for specific interventions and programs to improve their posture. On the basis of the results of this research, it is recommended to carry out cross-cultural research that would enable the comparison of results among children from different environments and cultural contexts in order to determine possible differences and particularities in the development of postural characteristics. Future research should include larger and more diverse samples of participants, including children from rural and urban areas, in order to ensure the representativeness and generalizability of the results. In addition, conducting a longitudinal study that would monitor the postural characteristics of children through different developmental stages is suggested, aiming to identify critical periods for intervention and to determine, more precisely, development trends within the context of gender differences.